Variability of temperature on the electrical properties of heterostructured CIS/Cds through SCAPS simulation for photovoltaic applications - Abass Akande Faremi; Olusayo Olubosede; Ayodeji Olalekan Salau; Samuel Olakunle Adigbo; Peter Apata Olubambi; Ezekiel Lawan (Materials for Renewable and Sustainable Energy, 2023)
Abstract Renewable energy research has received tremendous attention in recent years in a quest to circumvent the current global energy crisis. This study carefully selected and simulated the copper indium sulfur ternary compound semiconductor material with cadmium sulfide owing to their advantage in photovoltaic applications. Despite the potential of the materials in photovoltaic devices, the causes of degradation in the photovoltaic efficiency using such compound semiconductor materials have not really been investigated. However, electrical parameters of the materials such as open circuit voltage, short circuit current density, and fill factor have been extensively studied and reported as major causes of degradation in materials’ efficiency. Furthermore, identifying such electrical characteristics as a primary degradation mechanism in solar cells, this study work is an ardent effort that investigates the materials' electrical behavior as a cure to the degradation associated with compound semiconductor-based photovoltaic. In this study, we numerically characterized the electrical properties such as fill factor, open circuit voltage, short circuit current density, power conversion efficiency, net recombination rate, net generation rate, generation current density, recombination current density, hole current density, electrons current density, energy band diagram, capacitance–voltage, electric field strength of the heterostructured CIS/CdS compound semiconductor material using SCAP-1D. We also investigated the effect of temperature on the electrical properties of heterostructured materials. The obtained results reveal the uniformity of the total current density in the material despite the exponential decrease in the electron current density and the exponential increase in hole current density. The extracted solar cell parameters of the heterostructured CIS/CdS at 300 K are 18.6% for PCE, 64.8% for FF, 0.898 V for V oc, and 32 mA cm−2 for J sc. After the investigation of the effect of temperature on the CIS/CdS compound semiconductor material, it was observed that the solar cell was most efficient at 300 K. The energy band gap of the CIS/CdS compound semiconductor material shrinks with an increase in temperature. The highest net recombination rate and recombination current is at 400 K, while the net generation rate and generation current density are independent of temperature. The study, on the other hand, gave insights into the potential degradation process, and utilizing the study’s findings could provide photovoltaic degradation remediation.